2022
DOI: 10.32615/bp.2022.023
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of genes encoding enzymes involved in trehalose synthesis from Caragana korshinskii enhances drought tolerance of transgenic plants

Abstract: Trehalose, which plays important roles in resistance to abiotic stresses and preservation of biological activity in plants, is synthesized by two key enzymes, trehalose-6-phosphate synthase (TPS) and trehalose-6-phosphate phosphatase (TPP). Therefore, the expressions of the TPS and TPP genes directly affect trehalose synthesis and stress resistance of plants.In this study, CkTPS and CkTPP from Caragana korshinskii were identified, and the role of trehalose synthesis in the adaptation of this desert plant to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…The results demonstrated that ROS scavenging activity and the content of osmotic protectants such as soluble sugars and proline were higher than that of control and mock groups. These results were consistent with previous studies showing that the introduction of TPP genes activated the expression of stress-related genes participating in the antioxidant system and the production of osmotic protectants in other plants (Lin et al 2019;Huang et al 2022b;Lin et al 2023).…”
Section: Discussionsupporting
confidence: 93%
“…The results demonstrated that ROS scavenging activity and the content of osmotic protectants such as soluble sugars and proline were higher than that of control and mock groups. These results were consistent with previous studies showing that the introduction of TPP genes activated the expression of stress-related genes participating in the antioxidant system and the production of osmotic protectants in other plants (Lin et al 2019;Huang et al 2022b;Lin et al 2023).…”
Section: Discussionsupporting
confidence: 93%